Hashtag War in Gaza: An Analysis of the Role of Indonesian Citizens in #JulidFisabilillah from the Transnational Conflict Dimension - Qoirunnisa, Fentika Zahra; Mustofa, Mahmud Yunus (CONTENT: Journal of Communication Studies, 2024)
Abstract: The Israeli-Palestinian conflict not only has an impact on land but also extends to cyberspace. This research investigates the digital landscape of the Israeli-Palestinian conflict, specifically focusing on online activism surrounding the Gaza conflict. This research investigates the hashtag #JulidFisabilillah, a leading online movement originating from Indonesian citizens. Through comprehensive analysis, this research aims to uncover the motivations, narratives, and impacts of #JulidFisabilillah in the broader context of the Israeli-Palestinian War. By examining digital discourse, social media trends, and the role of Indonesian society in shaping online narratives, this research provides insight into the transnational dimensions of the conflict and the influence of digital activism on public opinion. These findings contribute to a deeper understanding of the role played by Indonesian netizens on online platforms in mobilizing global support and shaping perceptions during geopolitical conflicts.